How to improve the effectiveness of national cooperative organisations (New Delhi, 1981)
The major question before us was, is the cooperative move ment in a given country strong enough in every sense to initiate action, to promote, to organise and to support the growth of cooperatives which were being needed in many sectors of the developing economies. Every country in the region had a multi plicity of cooperative societies, servicing various economic needs within the community-but they were most often, loosely knit, both horizontally and vertically, the looseness of the structure itself most often being responsible for their weak performance. Federal structures on the business side did not provide that cohesive strength which would have improved their levels of performance and their competitive strength. What was a matter of grave concern was that the National Cooperative Organisation (N.C.O.) which was to be the spokesman of the movement itself often lacked adequate support and resources, both in terms of funds and personnel. As a result it could but play only a secondary role, often dependent on the roles assign ed to it by the government department concerned with coope rative development. It was felt that if the cooperatives were to emerge as a movement and play the role it was expected to play in the tremendous task of economic development and social rehabilitation, then the federal structures should be strengthened and above all positive steps should be taken to improve the effectiveness of the National Cooperative Organisations (NCO). It was with a view to developing suitable strategies to improve the effectiveness of the NCO that a regional seminar was concei ved of and conducted. At the initial stages we did encounter some difficulties in trying to define the term National Coopera tive Organisation to suit the situation in each country-this was found to be difficult as the practices varied and the basis of organisation differed from country to country.
Keywords: Cooperative organisations